Minimally modified low density lipoprotein stimulates monocyte endothelial interactions. - Berliner, J A (1990)
The effect of minimally modified LDL (MM-LDL) on the ability of large vessel endothelial cells (EC) to interact with monocytes and neutrophils was examined. These LDL preparations, obtained by storage or by mild iron oxidation, were indistinguishable from native LDL to the LDL receptor and were not recognized by the scavenger receptor. Treatment of EC with as little as 0.12 micrograms/ml MM-LDL caused a significant increase in the production of chemotactic factor for monocytes (sevenfold) and increased monocyte binding (three- to fivefold). Monocyte binding was maximal after 4 h of EC exposure to MM-LDL, persisted for 48 h, and was inhibited by cycloheximide. In contrast, neutrophil binding was not increased after 1-24 h of exposure. Activity in the MM-LDL preparations was found primarily in the polar lipid fraction. MM-LDL was toxic for EC from one rabbit but not toxic for the cells from another rabbit or any human umbilical vein EC. The resistant cells became sensitive when incubated with lipoprotein in the presence of cycloheximide, whereas the sensitive strain became resistant when preincubated with sublethal concentrations of MM-LDL. We conclude that exposure of EC to sublethal levels of MM-LDL enhances monocyte endothelial interactions and induces resistance to the toxic effects of MM-LDL.